Sermon preparation and delivery in an African context with special reference to Zambia - Chipwatanga, Laban Felix (University of the Free State, 1998)
Summary of sermon preparation and delivery in an African context with special reference to Zambia can be summarised as follows: This research has proved that there are great differences between the point of view of the African and the Westerner regarding the following topic: God, dreams, witchcraft and nature. The Westerner has one name for God but the African has many names for God. This creates a problem for the Westerner who does not understand whether or not the African is worshipping one God. There is also a difference regarding the understanding of dreams. The African believes that a dream is meaningful and a revelation from God (Number 12:6) but the Westerner believes that a dream is meaningless and occurs because of events which happened the day before the dream was dreamt. Witchcraft is regarded by the African as a reality, while the Westerner considers it to be unreal and merely telesthesia. Regarding nature, the difference is that the African considers nature to be part of his life while the Westerner looks at nature as an object to be admired and enjoyed only. • The study has revealed that effective African communication within an African community should adopt the African pattern of communication. Scriptural There is no other African foundation for preaching except the Scriptural one. African preaching is based on the Scriptures and anything other than this is supplementary information and should be treated as commentaries. Theological The African recognises holistic theology: the salvation for the whole person, but not the theory of the "salvation of the soul" which the Westerner embraces. The African believes in holistic Christianity and not in dualistic Christianity which the Westerner believes. Cultural The word of God is not received in a vacuum by the people receiving it. Therefore it was a mistake for the missionary (Westerner) to force the African Christian to receive God's Word in his culture rather than in his own African culture. This proves that the African culture should be introduced in the sermon preparation and delivery because the Word of God is received in the culture of the people hearing it. Pastoral Pastors' training should be contextualised in order that pastors should be well equipped for the local situations and problems of the people to whom they will minister. At present the training is more Western than African. For example, one should identify an African problem such like polygamy and then discuss it in class. Or a Western problem, like homosexuality can be discussed as the African sees it Biblically and culturally.

Die opsomming van preekvoorbereiding en voordrag in 'n Afrikaan-konteks met spesiale verwysing na Zambië kan as volg saamgevat word: • Hierdie navorsing het bewys dat daar groot verskille tussen die wêreldbeskouinge van die Afrikaan en die Westerling heers in verband met die volgende onderwerpe: God, drome, toorderyen die natuur. Waar die Westerling een naam vir God het, het die Afrikaan baie name. Die vele name veroorsaak 'n probleem vir die Westerling om te verstaan omdat dit onseker is of die Afrikaan een God aanbid, of nie. Daar is ook 'n groot verskil tussen die Westerling en die Afrikaan se beskouing van drome. Die Afrikaan glo dat 'n droom betekenisvol is en bestaan net as 'n gevolg van ondervindinge wat die vorige dag ervaar is. Toordery word deur die Afrikaan as 'n werklikheid beskou maar die Westerling beskou dit as onwerklik, en slegs as telesthesia. Hulle verskilook in hulle beskouing van die natuur. Die Afrikaan beskou die natuur as deel van sy lewe terwyl die Westerling dit beskou as 'n voorwerp om te bewonder en te geniet. • Die studie het ook aan die lig gebring dat effektiewe Afrikaankommunikasie binne 'n Afrikaan-gemeenskap behoort die Afrika-patroon van kommunikasie na te volg. Skriftuurlik Daar is geen ander grondslag vir die oordra van die Woord van God deur die Afrikaan as die skriftuurlike nie. Afrikaanprediking is gebaseer op die Bybel en enigeiets wat hiervan afwyk is aanvullende inligting en behoort net as kommentare behandel te word. Teologies Die Afrikaan erken 'n holistiese Christelikheid: die redding van die hele mens en nie net die "redding van die siel" nie, soos die Westerling glo. Die Afrikaan glo in 'n holistiese Christelikheid en nie in 'n dualistiese Christelikheid soos wat die Westerling glo nie. Kultureel Die Woord van God word nie in 'n lugleegte ontvang nie. Daarom het die sendeling (Westerling) fouteer toe hy die Afrikaan gedwing het om die Woord van God in sy kultuur in plaas van in die Afrikaan se eie kultuur te ontvang. Dit bewys dat die Afrikaan-kultuur behoort in die preekvoorbereiding en voordrag ingevoeg te word omdat die Woord van God in die kultuur van die mense wat dit aanhoor, ontvang word. Pastoraal Die pastoor se opleiding behoort binne verband gehou te word sodat hulle vir plaaslike toestande en vir die probleme van die mense vir wie hulle gaan dien, goed toegerus is. Tans is die opleiding meer Westers as Afrikaan. 'n Afrikaan-probleem behoort byvoorbeeld geïdentifiseer te word soos veelwywery en dan in die klas bespreek te word. Of die Westerse probleem van homoseksualiteit kan bespreek word soos die Afrikaan dit sien in die lig van die Bybel en sy kultuur.
Thesis (Ph.D. (Theology))--University of the Free State, 1998
Keywords: Preaching; Africa -- Religion; Christianity and culture -- Africa